Employee Competency Development Strategies for Improving Organizational Performance at Pertamina Balikpapan Hospital - Lita Ripiani; Edi Sugiono; Irma Setyawati (International Journal of Economics and Management Sciences, 2026)
Hospital employee competency development should be positioned as a strategic investment that connects individual capacity with service quality, patient safety, process efficiency, and organizational sustainability. This article analyzes competency development needs and formulates strategies applicable to Pertamina Balikpapan Hospital. The study employed a descriptive approach through a literature study and document review. The materials included national and international scientific articles, regulations, accreditation standards, books, corporate reports, and official websites published from 2022 to 2026. Data were examined using thematic content analysis through evidence grouping, organizational-needs mapping, strategy formulation, and evaluation-indicator development. The findings indicate that competency development should operate as an integrated cycle comprising job-based competency architecture, gap analysis, individual development plans, blended learning, simulation-based practice, coaching, mentoring, job rotation, digital competency strengthening, integration with performance and career management, and impact evaluation extending to organizational results. The strategy is organized into a three-stage road map covering foundation building, expansion and integration, and analytics-based optimization. Success should be measured through behavioral change, standards compliance, patient-safety indicators, patient experience, productivity, and succession readiness. The article concludes that Pertamina Balikpapan Hospital requires needs-based, interprofessional, documented competency-development governance directly connected to quality objectives. The proposed model provides an operational foundation for transforming training activities into measurable and sustainable drivers of organizational performance.